DISCLOSING THE FIRST PERSON NARRATOR IN EDGAR ALLAN POE’S THE BLACK CAT - Yulistiyanti Yulistiyanti (Dinamika Bahasa dan Budaya, 2017)
This research discussed on point of view applied in Edgar Allan Poe’s The Black Cat. It is a short story that Poe wrote using the first person narrator to tell it. This narrator needs to be explored the position, events of the story, and agenda which he hides. Qualitative research is applied to conduct this research. Edgar V. Roberts’ writing on point of view is the guide in conducting this research. The researchers need to read and identify the point of view, position of the narrator, events, and hidden agenda. It also needs to interpret the data found in The Black Cat text. The data show the first person narrator of The Black Cat put him as the unreliable narrator. It is based on the position in physical, mental, social, and economic circumstances that make the readers, here the researchers disbelieve in his utterances. The short story depicts eighteen events which involve the narrator as the major mover, the subject, and the main character of the story. It can be called that the information is the first hand experience that he wrote in a letter in a cell jail a day before he gets death sentence. This information leads the readers that he needs to get sympathy from his letter’s readers.Keywords: The Black Cat, point of view, first person narrator, unreliable